Pengaruh Brand Awarness Dan Brand Image Terhadap Minat Beli Ulang Produk Mie Instan Indomie Pada Konsumen Warmindo di Kota Kediri - Venalia Prayogo; Miftahul Munir; Nuril Aulia Munawaroh (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to explain the influence of brand awareness and brand image on repurchase interest at Warmindo, Kediri City. The data analysis technique used by researchers in this research uses statistical tests through validity tests, reliability tests, classical assumption tests, multiple linear regression tests, t tests, F tests with SPSS version 16.0 tools. The methods used in this research are questionnaires, interviews and observation. The sampling technique in this research used a saturated sample technique, with a total of 100 respondents. Based on the research results obtained by researchers from the multiple linear regression equation Y = -1,786 + 0.613X1 + 0.795X2. The results of the analysis carried out, the research results show that the brand awareness variable has a significant effect on repurchase interest with evidence that Sig t 0.000 < 0.05, the brand image variable has a significant effect on repurchase interest with evidence that Sig t 0.000 > 0.05, the variable discipline has a significant effect on repurchase interest with evidence of Sig t 0.000 < 0.05, and the results of brand awareness and brand image simultaneously have a significant effect on repurchase interest with evidence of Sig t 0.000 < 0.05. The results of the analysis value R2 = 0.949 or 94.9%.